Renal failure and its treatment. Issue 5 (May 2018) - Ng, Sarah; Hanison, James
Abstract: Acute kidney injury (AKI) is a common complication of acute illness. It is associated with significant morbidity and mortality as well as a high cost to healthcare systems. There are a broad range of causes of AKI which should be considered in a systematic fashion to avoid missing multiple potential causative factors. These include pre-renal causes from hypovolaemia, intrinsic renal causes such as glomerular diseases and post-renal obstructive causes. In the intensive care unit, two-thirds of AKI cases result from renal hypoperfusion, sepsis, contrast and nephrotoxic agents; up to 5% will require renal replacement therapy. Modalities of renal replacement therapy include intermittent haemodialysis, peritoneal dialysis and continuous haemofiltration. Continuous haemofiltration is usually favoured in the intensive care setting as it has greater haemodynamic stability and greater capacity to extract fluid from patients with fluid overload. Anticoagulation is recommended with haemodialysis and haemofiltration and systemic heparin, regional citrate or zero anticoagulation are the usual options.